Recent Advances in Hydrogel Dosage Forms for Local Therapy - Ali Zada, Mohammad Naeim; Shirzad, Qadir (Journal of Natural Sciences – Kabul University, 2024)
There are many limitations in the use of conventional dosage forms for the topical treatment of diseases, as drugs are quickly removed from the site of action and have lower bioavailability; thus, their delivery is ineffective. Hydrogels, as new dosage forms, can overcome many limitations associated with conventional dosage forms. Hydrogel dosage forms are hydrophilic polymer networks made from specific natural and synthetic polymers. These dosage forms can absorb large amounts of water and release drugs in a controlled manner. The aim of this review, which utilized reputable scientific sources, is to examine recent advances in hydrogel dosage forms used for topical therapy. Based on the findings, it is concluded that hydrogels can release drugs in a controlled manner by absorbing water, and these dosage forms are used for the topical treatment of superficial body parts (skin, eyes, nose, and vagina).